Pengaruh Brand Image dan Kualitas Pelayanan Terhadap Kepuasan Konsumen ZARA di Jakarta - Maudy Cesar Novrilya; Mariah (UNIVERSITAS KALBIS, 2022)
The purpose of this study was to determine the effect of brand image and service quality on ZARA's consumer satisfaction in Jakarta. This study uses a quantitative method which is processed using SPSS 25 through a questionnaire distributed to 100 respondents using a purposive sampling method. The test results show that partially there is an influence of brand image and service quality on customer satisfaction. Simultaneously the influence of brand image and service quality on consumer satisfaction. This research was conducted to provide an understanding for ZARA in Jakarta to pay attention to brand image, service quality, and customer satisfaction.